Atenção odontológica no Programa Saúde da Família (PSF)de Campos de Goytacazes - RJ após um ano de implantação: a visão dos atores sociais envolvidos - Oliveira, José Luiz Carvalho de [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
Oral health policy in Brazil has been centred on giving assistance to diseases for decades and a great portion of the Brazilian population has not already had access to dental care. Thus, the Family ´s Health Programme (FHP) comes up having as objective to re-orient the Brazilian Assistance Model, aiming mainly at promoting the quality of life. Having the same target, through Edict 1444, dated 28th December 2000, the Health Ministry established a financial incentive for attention re-organisation given to oral health in municipalities. Thus, Dentistry is inserted in that programme and, consequently, the possibility of enlarging and re-orienting dentistry attention in Brazil. In this context, this research aimed at evaluating the situation of oral health teams inserted in the Family ´ s Health Programme in the city of Campos dos Goytacazes, Rio de Janeiro State, Brazil, in 2002 – Reorganisation of Oral Health Actions concerning dentistry attention. This work was performed encompassing the following people involved in services of the Family ´s Health Programme : dentistry, oral hygienists, dental auxiliary and patients.Related to the methodology, quantitative and qualitative approaches, worried with understanding the meaning given by the research subjects to the studied issues, were developed, so that it could be possible to characterise descriptions and quotations on their experiences, hopes, attitudes and thoughts on the subject matter. The research was accomplished in Campos dos Goytacazes City, Rio de Janeiro State, Brazil, in 2002 in basic health offices where oral health teams worked. The results show some limitations related to inclusion and working of Dentistry at the FHP in that city. Dentistry attention must be attached to the FHP, in accordance with the basic principles of the Re-structuring Oral Health Action Plan in the Basic Attention proposed by the Health Ministry ...

La politique de la santé buccale au Brésil a été, pendant décades centrée dans la prestation d’assistance à la maladie, et grande parcelle de la population brésilienne n’a pas encore l’accès aux soins de L’Odontologie alors, le Programme de la Santé de la Famille (PSF) surgit, en ayant comme objectif réorienter le modèle d’assistance brésilienne, en objectivant, principalement, la promotion de la qualité de vie. Et, c’est avec ce même but que, par l’ordonnance 1.444 le 24 décembre 2000, le Ministère de la Santé établit le stimulant financier pour la réorganisation de l’attention à la santé buccale aux municipes. L’Odontologie s’insàre, ainsi, dans le programme y compris avec la prestation de services d’odontologie dans le Programme de Santé de la Famille: chirurgiens-dentistes, de bureau de consultation d’odontologie et technique d’hygiène dentaire et les utilisateurs qui cherchent les services d’odontologie. Par rapport la méthodologie, il a eu dévelopée unabordage qualiquantitatif, en se préocupant avec la compréhensaon de la signification atribuée par les sujets aux questions étudiées, de manière à caracteriser la description et citations sur les expériences, les expectatives, les attittudes et les pensées sur le sujet. La recherche a eu realisée dans le municipe de Campos dos Goytacazes – RJ dans l’année 2002, dans les unités de base de santé buccale. Les résultats démonstrent quelques limitations dans l’inclusion et fonctionnement de l’odontologie no PSF de Campos dos Goytacazes. L’attention d’Odontologie doit être inserée no PSF...

A política de saúde bucal no Brasil foi durante décadas, centrada na prestação de assistência à doença, e grande parcela da população brasileira ainda não tem acesso a cuidados odontológicos. Surge, então, o Programa de Saúde da Família (PSF), tendo como objetivo reorientar o modelo assistencial brasileiro, visando, principalmente, à promoção da qualidade de vida. E é com este mesmo intento que, através da Portaria 1.444 de 28 de dezembro de 2000, o Ministério da saúde estabelece incentivo financeiro para a reorganização da atenção à saúde bucal aos municípios. Insere-se, assim, a Odontologia no Programa e, conseqüentemente a possibilidade de ampliar e reorientar a atenção odontológica no Brasil. Dentro deste contexto, esta pesquisa teve por objetivo avaliar a situação da equipe de saúde bucal inserida no Programa de Saúde da Família do município de Campos dos Goytacazes – Rio de Janeiro, em 2002, considerando se a inclusão atende ao documento emitido pelo Ministério da Saúde em 2000 – Reorganizaçãodas Ações de Saúde Bucal na Atenção Odontológica. Este trabalho foi realizado com quatro atores sociais envolvidos com a prestação de serviços odontológicos no Programa de Saúde da Família: cirurgiões-dentistas, atendentes de consultório odontológico e técnico de higiene dentária e os usuários que buscaram os serviços odontológicos. Quanto à metodologia, foi desenvolvida uma abordagem quali-quantitativa, preocupando-se com o entendimento do significado atribuído pelos sujeitos às questões estudadas, de maneira a caracterizar descrições e citações sobre suas experiências, expectativas, atitudes e pensamentos em torno do assunto. A pesquisa foi realizada do município de Campos dos Goytacazes-RJ no ano de 2002, nas unidades básicas de saúde onde atuavam as equipes de saúde bucal. Os resultados demonstraram algumas limitações ....
Keywords: Saúde pública; Saúde bucal; Public health; Family's health program; Santé publique